TEXTURE CHARACTERIZATION OF THE COPPER PRODUCED BY ECAP PROCESS USING NEUTRON DIFFRACTION TECHNIQUE - M. R. Muslih; T. H. Priyanto; M. Rifai; Andryansyah; R. Riastuti (BRIN Publishing (Penerbit BRIN), 2022)
TEXTURE CHARACTERIZATION OF THE COPPER PRODUCED BY ECAP PROCESS USING NEUTRON DIFFRACTION TECHNIQUE. Texture and hardness characterization have been carried out on market copper samples that have gone through the equal channel angular pressing (ECAP) process. Neutron diffraction technique had been used for obtaining an average crystalline texture in a particular volume non destructively to the sample. The ECAP process is carried out once (1 pass) with some parts that have been plastically deformed and some parts that have not been deformed. Crystalline texture and hardness were observed in the deformed and non-deformed parts. Initial characterization was carried out by X-ray diffraction (XRD) followed by measurement of crystal texture using the neutron diffraction technique, while hardness was tested using the Vickers method. Rod-shaped sample with a diameter of 10 mm. Texture observations were performed at the center of the sample with a neutron beam limiting slit of 5x5 mm2 . There was an increase in hardness in the deformed position compared to the undeformed one. The texture that occurs is in the form of fibers with different directions and indexes, sequentially as follows: position 1, [111] of 4.96 m.r.d., position 2, -[111] of 1.86 m.r.d. and position 3 [010] of 2.44 m.r.d. , position 4 orientation is distributed on [011], [013], [115], [235] fibers with a texture index range of 1.07–1.33 m.r.d.